Respiratory reoxidation of NADH is a key contributor to high oxygen requirements of oxygen-limited cultures of Ogataea parapolymorpha. Issue 1 (7th February 2022) - Dekker, Wijbrand J C; Jürgens, Hannes; Ortiz-Merino, Raúl A; Mooiman, Christiaan; van den Berg, Remon; Kaljouw, Astrid; Mans, Robert; Pronk, Jack T
Abstract: While thermotolerance is an attractive trait for yeasts used in industrial ethanol production, oxygen requirements of known thermotolerant species are incompatible with process requirements. Analysis of oxygen-sufficient and oxygen-limited chemostat cultures of the facultatively fermentative, thermotolerant species Ogataea parapolymorpha showed its minimum oxygen requirements to be an order of magnitude larger than those reported for the thermotolerant yeast Kluyveromyces marxianus . High oxygen requirements of O. parapolymorpha coincided with a near absence of glycerol, a key NADH/NAD + redox-cofactor-balancing product in many other yeasts, in oxygen-limited cultures. Genome analysis indicated absence of orthologs of the Saccharomyces cerevisiae glycerol-3-phosphate-phosphatase genes GPP1 and GPP2 . Co-feeding of acetoin, whose conversion to 2, 3-butanediol enables reoxidation of cytosolic NADH, supported a 2.5-fold increase of the biomass concentration in oxygen-limited cultures. An O. parapolymorpha strain in which key genes involved in mitochondrial reoxidation of NADH were inactivated did produce glycerol, but transcriptome analysis did not reveal a clear candidate for a responsible phosphatase. Expression of S. cerevisiae GPD2, which encodes NAD + -dependent glycerol-3-phosphate dehydrogenase, and GPP1 supported increased glycerol production by oxygen-limited chemostat cultures of O. parapolymorpha . These results identify dependence on respiration for NADH reoxidation as a key contributor to unexpectedly high oxygen requirements of O. parapolymorpha . Abstract : Large oxygen requirements of the industrially relevant yeast O. parapolymorpha in oxygen-limited cultures were attributed to a necessity to reoxidize surplus NADH from biosynthetic reactions by mitochondrial respiration ('Custers effect').